Strengthening the Concept of Parenting in the Modern Era: A Study of al-Qur’an Surah at-Tahrim Verse 6 on Child Parenting - Elitaliya, Muthia Fitri; Surahman, Cucu; Islam, Rindu Fajar (Islamic Religious Education Departement, 2025)
This study explores the relevance of QS At-Tahrim verse 6 in parenting in the modern era, which faces challenges from social and technological changes. The main focus is on how Islamic parenting methods can be adapted to contemporary life demands and how this verse can serve as a foundation for developing a relevant parenting concept today. Using library research methods and a descriptive analysis approach, the study utilizes literature such as Quranic exegesis and scholarly articles on Islamic parenting. Through Tahlili and ijmali exegesis, the research finds that this verse emphasizes the role of parents in protecting themselves and their families from the fire of Hell through strict religious education and supervision of children. The study links these Islamic parenting principles with modern parenting models, such as positive and authoritative parenting, which share similarities in supervision, discipline, and communication. The conclusion is that QS At-Tahrim verse 6 is relevant for modern parenting and provides guidance in shaping a generation that is strong both spiritually and intellectually.